AI-Driven Ethical Pricing: Balancing Profitability and Social Responsibility - Karthik Ramakrishnan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative potential of AI-driven ethical pricing in addressing economic disparities while maintaining business viability. It examines how advanced machine learning algorithms and data analysis can create fair and accessible pricing strategies across various sectors, including pharmaceuticals, utilities, and digital platforms. The paper discusses the theoretical framework underlying these approaches, including socio-economic data analysis and the implementation of sliding-scale and tiered pricing structures. It also delves into the challenges of ensuring unbiased AI systems, maintaining transparency, and balancing profitability with social impact. The benefits of ethical pricing, such as enhanced brand reputation and contribution to societal well-being, are explored through real-world case studies. Looking towards the future, the article outlines research opportunities in areas like blockchain integration, personalized pricing models, and cross-industry collaboration. Ultimately, this comprehensive examination demonstrates how AI-driven ethical pricing can foster a more equitable marketplace, potentially reshaping economic landscapes and improving access to essential goods and services for diverse populations.